Direct 2D cement-nanoadditive deposition enabling carbon-neutral hydrogen from natural gas. (August 2022) - Chen, Shu Jian; Zhang, Qianhui; Nguyen, Hoan D.; Ren, Yizhen; Liu, Yanming; Wang, Wei; Gao, Wenchao; Ren, Jiawei; Sagoe-Crentsil, Kwesi; Duan, Wenhui
Abstract: Currently, hydrogen is mainly produced by conversion from natural gas via steam methane reforming (SMR), generating massive amounts of CO2 . Here, we present a novel production scheme that can neutralize the CO2 from natural gas-based hydrogen productions by direct deposition of 2-dimensional carbon as cement-nanoadditive. Our tests demonstrated that cement-compatible particles can be used effectively as substrates to grow carbon nanosheets. Our analysis showed that the scheme, bridging hydrogen and cement industries, translates a ~268.7 tons cement reduction per ton of produced hydrogen with > 99% reduction of carbon nanosheets costs. Correspondingly, 375.5 Mt CO2 generated from the current SMR-based hydrogen production in the USA, China, and Australia could be neutralized by adopting this approach. We showed that combining CO2 capture in SMR and 5% replacement by our scheme can produce carbon-neutral hydrogen to meet the predicted global demand in 2045. Graphical Abstract: ga1 Highlights: Carbon nanosheets was directly deposited on cement-compatible substrates during methane-hydrogen conversion. A bridging scheme between hydrogen and cement industries was proposed. Highly carbon negative was obtained using our method. Our approach can provide carbon-neutral natural gas-based hydrogen to meet the global demand in 2045.